Cannabis and crash risk among older drivers. (March 2021) - Johnson, Mark B.; Mechtler, Laszlo; Ali, Bina; Swedler, David; Kelley-Baker, Tara
Highlights: Older THC-positive drivers were at increased risk for crash. Younger and middle-aged THC-positive drivers were not at increased risk. Analysis controlled for alcohol and excluded polydrug users. Abstract: The purpose of this research was to reanalyze data collected from the National Highway Traffic Safety Administration's Drug and Alcohol Crash Risk Study to investigate whether driving under the influence of cannabis (THC-positive) was associated with elevated crash risk for younger and older drivers. The data came from a case-control relative risk study collected from Virginia Beach, VA, over a 20-month period. Data collectors gathered driver information from the scene of vehicle crashes and, in some cases, from hospitals. Non-crash controls were sampled from the same locations, days, and times as crashes. Key data items included driver demographics and oral fluid and blood samples, which were assayed for licit and illicit drugs. We found no overall association between cannabis use and risk of crash involvement. However, when age and age 2 were allowed to interact with THC, significant interaction effects emerged. THC was associated with increased risk of crash involvement for older drivers. Difference between THC-positive and sober drivers emerged as significant at age 64. The research underscores the value of examining drugged driving in the context of driver age. Age-related declines in neurocognitive and psychomotor functioning were not measured but might be important in explaining the results.